Dream big starring Olivia - Falconer, Ian 1959-. (Kansas City Andrews McMeel, 2006)
Olivia dreams big. Whether she's taming a circus lion or building a sandcastle as tall as the Empire State Building, her boundless imagination and courageous spirit are an inspiration to young and old...
Collection of quotations with illustrations of Olivia.
Keywords: Conduct of life -- Quotations, maxims, etc